THE EFFECT OF PASSING TO THE WALL EXERCISE ON THE RESULTS OF PASSING IN MEN'S VOLLEYBALL - Aji, M Bagas Prasetyo; Syafaruddin, Syafaruddin; Destriana, Destriana (Journal Physical Education, Health and Recreation, 2023)
The purpose of this study was to determine the effect of overhead passing to the wall on the results of overhead passing in extracurricular volleyball games at SMK Negeri 1 Gelumbang. The method used was a quasy experiment with a pretest-posttest one group design. The sample of this study consisted of 20 people, namely 20 male students who took part in the volleyball extracurricular at SMK Negeri 1 Gelumbang. The instrument used is the upper passing test. The treatment in this study was in the form of overhead passing to the wall, treatment for 4 weeks from March 15-April 15 with a training frequency of 4 times a week. Based on the results of the study, the top-to-the-wall passing exercise in extracurricular volleyball games at SMK Negeri 1 Gelumbang with a t-test result for men with a tcount of 15.57 and a ttable of 2.09 (df 19) with a significance value of p is 0.000. Tcount 15.57 > ttable 2.09, and a significance value (2-tailed) 0.000 <0.05, so these results show that there is a significant difference. It was seen that there was an increase after the treatment was carried out, it was stated that there was a significant effect of the top passing exercise to the wall in the extracurricular men's volleyball game at SMK Negeri 1 Gelumbang. The implication of this study is that the overhead pass to the wall exercise can be used as a type of exercise to improve upper passing in volleyball.